GRAMATIKALISASI VERBA HEIN DAN SEIN - Ridwan, Agus (Paramasastra: Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2016)
Linguistic units in any language will develop at a certain time. Such development can occur in the field of phonology, (morpho) syntax, and semantics. However, not all of linguistic units can develop in parallel on these three areas. It also occurs at the language units of German like verbs haben ‘have’ and sein ‘to be’. The verbs haben ‘have’ and sein ‘to be’ can have function as a full verb. In addition to a full verb, the verbs haben ‘have’ and sein ‘to be’ also serve as an auxiliary verb, a functional verb and a modality verb. The various functions of verbs especially the origin of their formation certainly created problems for language expert and observer, and also German language teachers/learners. In connection with the issue, this article tries to describe the development of verbs haben ‘have’ and sein ‘to be’. The theory used in the analysis is the theory of grammaticalization in the field of syntagmatic/paradigmatic (morpho) syntax and semantics.